2012
DOI: 10.1002/jbm.a.34017
|View full text |Cite
|
Sign up to set email alerts
|

Increased new bone formation with a surface magnesium‐incorporated deproteinized porcine bone substitute in rabbit calvarial defects

Abstract: This study investigated the effects of magnesium ion (Mg) incorporation into the surface of deproteinized porcine cancellous bone in the bone healing of rabbit calvarial defects with the expectation of utilizing the integrin-ligand binding enhancement effect of Mg, and compared its bone healing capacity with that of untreated porcine cancellous bone and deproteinized bovine bone (Bio-Oss). Hydrothermal treatment was performed to produce Mg-incorporated porcine bone using an alkaline Mg-containing solution. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 38 publications
1
29
0
2
Order By: Relevance
“…Magnesium, its alloys [10][11][12][13] and derivatives [14][15][16] have been extensively studied as replacements for non-degradable metallic implants e.g., titanium alloys in bone surgeries. Mg 2+ modified biomaterials have shown superior osteogenic capacity in many reports [14][15][16][17][18][19][20][21] . However, the detrimental effects of Mg 2+ released upon degradation have also been observed [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium, its alloys [10][11][12][13] and derivatives [14][15][16] have been extensively studied as replacements for non-degradable metallic implants e.g., titanium alloys in bone surgeries. Mg 2+ modified biomaterials have shown superior osteogenic capacity in many reports [14][15][16][17][18][19][20][21] . However, the detrimental effects of Mg 2+ released upon degradation have also been observed [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…Other xenograft materials from the other origins (swine and equine) have been introduced in the clinical and research fields of dentistry under the banner of prevention of the bovine‐specific disease transmission . Although no clinicians have reported disease transmission related to this method since DBBM was first used several decades ago, a recent systematic review indicated a possible risk of disease transmission related to prions .…”
Section: Introductionmentioning
confidence: 99%
“…Other xenograft materials from the other origins (swine and equine) have been introduced in the clinical and research fields of dentistry under the banner of prevention of the bovine-specific disease transmis-sion. [10][11][12][13][14] Although no clinicians have reported disease transmission related to this method since DBBM was first used several decades ago, a recent systematic review indicated a possible risk of disease transmission related to prions. 15 Deproteinized porcine bone mineral (DPBM) is one substitute for DBBM, and several researchers already introduced DPBM for clinical dental procedures [16][17][18][19] based on the structural/ physiological similarities of bone tissue between human and swine.…”
Section: Introductionmentioning
confidence: 99%
“…Hussain et al 43 incorporated different concentrations of magnesium phosphate calcium (MCP) into gelatin sponges and prepared MCP gelatin scaffolds that could promote the healing of calvaria defects in rats. Additionally, Park et al 44 prepared deproteinized porcine cancellous bone incorporated with Mg on the surface with which the rabbit calvaria defect could be better healed after implantation. Yoshizawa et al 45 attributed these promoting effects to Mg incorporation with higher level of osteogenesis-related genes and mineralization when treating hBMSCs with MgSO 4 at different concentrations.…”
mentioning
confidence: 99%